Clinical and Prognostic Analysis of Autoantibody-Associated CNS Demyelinating Disorders in Children in Southwest China - Li, Ziyan; Sun, Hong; Fan, Xiao; Yuan, Ping; Jiang, Yan; Wu, Peng; Zhong, Min; Ma, Jiannan; Jiang, Li; Li, Xiujuan (Frontiers in Neurology, 2021)
Objective: To analyze the positive rate and the recurrence rate of different autoantibody-associated demyelination in Southwest China, to describe clinical, radiological and prognostic features of myelin oligodendrocyte glycoprotein antibodies (MOG-Ab) and aquaporin-4 antibodies (AQP4-Ab) disease, and to summarize the steroid maintenance therapy for MOG Ab-associated disorders. Methods: A total of 174 children presenting with ADS from January 2016 to December 2019 were tested MOG-Ab, AQP4-Ab and oligoclonal bands (OCBs). Clinical data, MRI scans and survival analysis were compared between MOG-Ab positive and AQP4-Ab positive children. Temporal evolution of serologic status and treatment response on immunosuppressants were collected in children with MOG-Abs. Results: Of the 174 included children, positive rate for MOG-Ab (47.7%) was significantly higher than that of AQP4-Ab (5%) and OCBs (2.7%), recurrence rate for AQP4-Ab (71.4%) was higher than that of MOG-Ab (30.1%) and OCBs (33.3%). For 118 children with all MOG-Ab, AQP4-Ab and OCBs tested, their median age at onset was 7 (IQR 5-10) years, and their median follow-up period was 19 (IQR 13-27.5) months. MOG-Ab positive children more frequently presented with acute disseminated encephalomyelitis, and had deep grey matters lesions on MRIs, better clinical and radiological recovery, and was less likely to have sustained disability than AQP4-Ab positive children. In children with MOG-Abs and AQP4-Abs, maintenance therapy was a protective factor for recurrence, but presenting optic neuritis was a predictor of sooner relapse. A high EDSS score at onset was associated with sustained disability. The steroid maintenance therapy longer than 6 months after the initial attack was related to a lower risk of a second relapse in MOG-Ab positive children. On serial serum MOG antibodies analysis, clinical relapse occurred in 34.6% of children with persistently seropositive, but none of children who converted to seronegative experienced relapse. Conclusion: MOG-Ab is more common in children with ADS than AQP4-Ab and OCBs. MOG-Ab-associated disorders is characterized with distinct clinical and radiological features. Although some MOG-Ab positive children experience relapsing courses or had persistently seropositive status, MOG antibody-associated disorders still predict a better outcome than AQP4-Ab NMOSDs.